(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article covers the application of differential calculus in practical problems. It provides specific examples in the fields of finding extreme values of functions, optimization, physics (movement, velocity, projectile range), economics (maximizing profit, minimizing costs), and geometry (minimizing surfaces). Each example is explained with step-by-step solutions, which shows the practical significance of theoretical knowledge.